أثر تداخل مسميات دلالة المفهوم في المسائل الأصولية - وخام, سفيان (University of Eloued جامعة الوادي, 2019)
عالجت في هذا البحث التداخل الحاصل بين مسميات دلالة المفهوم عند الأصوليين، سواء تعلق ذلك بتداخل مسمى دلالة المفهوم بغير جنسه، أم بتداخل مسماه بجنسه، فتناولت جميع ذلك تناولا مقارنا من جهات مختلفة، منها ما يتعلق بجهة حقيقة المفهوم ومنها ما يتعلق بجهة التخصيص؛ ومنها ما يتعلق بالمفهوم من جهة أنواعه، على أنّني ذكرت إثر كل صورة من صور هذا التداخل ما ينتج عنه من الآثار المعنوية أو اللفظية التي قد تتأثر بها بعض المسائل الأصولية. . In this research, I dealt with the overlap between the names of the concep connotation among the fundamentalists, whether it's related to the overlap of the connotation of the concept of meaning without gender, or by overlapping its name with its gender, so I took up all of this and compared them in different ways, Some of them are related to the reality of the concept and some related to the allocation; Some of them are related to the concept in terms of its types, however, after each form of this overlap, I mentioned the resulting moral or verbal effects that may affect some fundamentalist issues.
دراسة مقارنة في أصول الفقه الإسلامي
مقال بمجلة الشهاب
Keywords: المنطوق ; المفهوم ; التخصيص ; الصفة ; العدد ; الغاية; concept, operative, allocation, adjective, number, purpose.